2016
DOI: 10.1111/iju.13067
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic model to predict survival in patients with metastatic upper tract urothelial carcinoma treated with cisplatin‐based chemotherapy

Abstract: Abbreviations & AcronymsObjectives: To create a novel prognostic model to predict survival in metastatic upper tract urothelial carcinoma patients treated with cisplatin-based chemotherapy. Methods: After institutional review board approval, patients who had metastatic upper tract urothelial carcinoma and were treated with cisplatin based chemotherapy from 2000 to 2012 at Kaohsiung Chang Gung Memorial Hospital were retrospectively reviewed. Significantly predictive factors were identified by multivariate Cox r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“… 16 Hsieh et al reported that cisplatin‐fit renal function (CrCl > 60 mL/min) was an independently good prognostic factor for metastatic UTUC patients treated with cisplatin‐based chemotherapy (MVAC; N = 63, GC; N = 73). 17 The dose reduction protocol for the cisplatin‐based regimen was not clarified in this study either. Compared with previous reports, our cohort study was organized by a single GC regimen under unified protocol of reduced cisplatin with more metastatic UC patients.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“… 16 Hsieh et al reported that cisplatin‐fit renal function (CrCl > 60 mL/min) was an independently good prognostic factor for metastatic UTUC patients treated with cisplatin‐based chemotherapy (MVAC; N = 63, GC; N = 73). 17 The dose reduction protocol for the cisplatin‐based regimen was not clarified in this study either. Compared with previous reports, our cohort study was organized by a single GC regimen under unified protocol of reduced cisplatin with more metastatic UC patients.…”
Section: Discussionmentioning
confidence: 97%
“…This retrospective study consists of different types of regimens which include only three cases of MVAC and GC in the reduced dose group 16 . Hsieh et al reported that cisplatin‐fit renal function (CrCl > 60 mL/min) was an independently good prognostic factor for metastatic UTUC patients treated with cisplatin‐based chemotherapy (MVAC; N = 63, GC; N = 73) 17 . The dose reduction protocol for the cisplatin‐based regimen was not clarified in this study either.…”
Section: Discussionmentioning
confidence: 99%